Who visits the Kruger National Park, and why? identifying target markets. Issue 3 (24th March 2017) - Kruger, Martinette; Viljoen, Armand; Saayman, Melville
ABSTRACT: This study identified viable target markets at South Africa's most renowned nature reserve, the Kruger National Park, using market segmentation based on demographic characteristics. International, domestic, and local nature tourists were surveyed and categorized into three distinct clusters. The results show that block clustering based on visitors' demographic characteristics is a useful research tool for producing a clear visitor profile and showed that during the process of market segmentation it is necessary to establish the relationship between a particular segmentation base and visitors' behavior and preferences. This is useful information for managing this Park, and other similar parks, more sustainably.